Botanical traceability of commercial tannins using the mineral profile and stable isotopes†. (10th September 2014) - Bertoldi, Daniela; Santato, Alessandro; Paolini, Mauro; Barbero, Alice; Camin, Federica; Nicolini, Giorgio; Larcher, Roberto; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> Commercial tannins are natural polyphenolic compounds extracted from different plant tissues such as gall, the wood of different species and fruit. In the food industry they are mainly used as flavourings and food ingredients, whereas in winemaking they are classified as clarification agents for wine protein stabilisation, although colour stabilisation, metal removal, unpleasant thiol removal and rheological correction are also well‐known and desired effects. Due to their particular technical properties and very different costs, the possibility of correct identification of the real botanical origin of tannins can be considered a primary target in oenology research and in fulfilling the technical and economic requirements of the wine industry. For some categories of tannins encouraging results have already been achieved by considering sugar or polyphenolic composition. For the first time this work verifies the possibility of determining the botanical origin of tannins on the basis of the mineral element profile and analysis of the 13C/12C isotopic ratio. One hundred two commercial tannins originating from 10 different botanical sources (grapes, oak, gall, chestnut, fruit trees, quebracho, tea, acacia, officinal plants and tara) were analysed to determine 57 elements and the 13C/12C isotopic ratio, using inductively coupled plasma mass spectrometry and isotope‐ratio mass spectrometry, respectively. Forward stepwise discriminant analysis provided good discrimination between the 8 most abundant groups, with 100% correct re‐classification. The model was then validated five times on subsets of 10% of the overall samples, randomly extracted, achieving satisfactory results. With a similar approach it was also possible to distinguish toasted and untoasted oak tannins as well as tannins from grape skin and grape seeds. Copyright © 2014 John Wiley & Sons, Ltd.